Dossier: Literature, Masculinities and Sexual Diversity (Anclajes, 2018)
Presentation and description of the texts that shape the present dossier, linked to literary studies, on the one hand, and studies on masculinities and sexualdiversity in Argentina, Mexico and Spain, on the other hand.
Keywords: Literature; Gender Studies; 20th and 21st Centuries; Argentina; Mexico and Spain